2021
DOI: 10.3389/fnins.2021.660379
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Dysregulation in Parkinson’s Disease: A Narrative Review

Abstract: Parkinson’s disease (PD) is a severely debilitating neurodegenerative disease, affecting the motor system, leading to resting tremor, cogwheel rigidity, bradykinesia, walking and gait difficulties, and postural instability. The severe loss of dopaminergic neurons in the substantia nigra pars compacta causes striatal dopamine deficiency and the presence of Lewy bodies indicates a pathological hallmark of PD. Although the current treatment of PD aims to preserve dopaminergic neurons or to replace dopamine deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 144 publications
0
50
0
1
Order By: Relevance
“…miR-494 bind PARK7 3 UTR reducing its expression. Very interestingly this miRNA is highly upregulated both in plasma and saliva of PD patients [75].…”
Section: Mirnas Involved In the Pathogenesis Of Pdmentioning
confidence: 99%
See 4 more Smart Citations
“…miR-494 bind PARK7 3 UTR reducing its expression. Very interestingly this miRNA is highly upregulated both in plasma and saliva of PD patients [75].…”
Section: Mirnas Involved In the Pathogenesis Of Pdmentioning
confidence: 99%
“…It has been shown that there are miRNAs involved in the regulation of SNCA expression and accumulation. Among them, miR-7a and miR-153 are able to post-transcriptionally regulate the expression of SNCA: miR-7a inhibits its translation, whereas miR-153 degrades its mRNA [75]. In particular, depletion of miR-7a is related with SNCA accumulation and neuron loss in vivo [76].…”
Section: Mirnas Involved In the Pathogenesis Of Pdmentioning
confidence: 99%
See 3 more Smart Citations